Strategies for Improved Handicrafts Exports - Subramaniam, D. (Prabandhan: Indian Journal of Management, 2012)
In the current globalized economy, there is a market for every product. Any organization /country can identify the products that provide them a competitive advantage to engage themselves in export of that product. Handicrafts are one such category of items that have a huge potential for export, especially in the Indian Context. This is essentially because handicrafts cover a wide range of products. India is a nation with a strong cultural background - where diverse geographical areas come out with unique handicrafts of their own, which are very difficult to imitate, where technology cannot have a major role, and where the experience of the artisan is highly critical - all these factors provide a crucial competitive advantage. These factors also act as an entry barrier for the competitors. In spite of such competitive advantages, the Indian handicrafts export is just about 2% of the world market, as compared to 17% of China in the world trade. The present paper attempts to study the challenges in this regard and suggests focus areas for action.